Management of small ruminant production systems in the farming areas of Kenya - Gathuka, Z.G. (1986)
In Kenya the existing sheep and goat production systems are associated with ecozones, land organization and social economic factors. Also the interaction between these factors give rise to the three-production system viz. Smallholder, large-scale ranching, and rage pastoralism including nomadism. The total population of goats and sheep is approximately 15 million, of which 8.2 million is kept by the pastoralists, 6.4 million by the small-scale sedentary agriculturalists and 0.4 million by the commercial ranches. The indigenous breeds dominate the pastoral system while the wool sheep and improved breeds of meat goats and sheep are kept by the large-scale farmers. The small-holder farmers keep different types of small stock for meat, milk and wool.